Designing Worship Together: Models And Strategies For Worship Planning - Malefyt, Norma deWaal; Vanderwell, Howard (Rowman & Littlefield Publishers, 2004)
Much more than a "how-to" for worship planners. Drawing on more than two decades of collaborative worship planning, as well as numerous conversations with other worship planners. Pastor Howard Vanderwell and musician Norma de Waal Malefyt lay out a thoughtful, field-tested process for planning, implementing, and evaluating life-enriching weekly worship. Well over a dozen field-tested tools and a selected bibliography round out this invaluable resource for worship planners.